Enzymatic saccharification of peat polysaccharides is limited by accessibility. - Jonas Thomsen; Signe Lett; Helle J Martens; Helle Sørensen; Darragh Kelleher; Theodora Tryfona; Paul Dupree; Katja S Johansen (PLoS ONE)
Sphagnum peat bogs store a large fraction of biologically-bound carbon, due to a steady accumulation of plant material over millennia. The resistance of Sphagnum biomass to decay is poorly understood and of high importance for preservation efforts and climate models. Sphagnum peat mostly consists of the polysaccharide-rich cell wall of the moss but the mechanisms by which it resist degradation by microbes remain unclear. Here we show that enzymatic saccharification of peat polysaccharides including cellulose and other glucose-rich polysaccharides is predominantly limited by access to the substrate. The experimental approach involved biotechnological tools including hydrothermal pretreatment to disrupt and relocate cell wall components. This physical change was confirmed by confocal laser scanning microscopy. A cocktail of microbial enzymes (Cellic® CTec3) designed for industrial saccharification of lignocellulose of vascular plants was used to assess enzymatic digestibility of peat polysaccharides. The glucose yield increased from close to zero for untreated peat to 30% and 50% when pretreated at 160 and 180 °C. An overall catalytic rate constant for enzymatic glucose-release from peat-cellulose of 26.98 h-1 was calculated using a kinetic model. This is a similar or higher rate compared to cellulose from vascular plant tissues. With an iron content of 2 g/kg dry peat, oxidative inactivation of enzymes is an important factor to take into account. A high inactivation constant of 125.91 x10-3 h-1 was found for the used saccharification conditions, but the addition of catalase alleviated the oxidative inactivation and increased the glucose yield with 60% in peat pretreated at 180 °C. These findings show that molecular structures of Sphagnum peat which prevents access for cell wall degrading enzymes can be disrupted by hydrothermal pretreatment. This brings us closer to understanding peat recalcitrance and thus how very large amounts of organic carbon is stored.